Analisis Campur Kode dalam Whatsapp Grup Pertukaran Mahasiswa - Ade Novita Sari Hutabarat (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
The purpose of this study is to describe the types of code mixing that occur in the independent student exchange group whatsapp group 1. The data source in this study is the conversation of exchange students who are members of the whatsapp group. This study uses a qualitative descriptive method, namely research that produces descriptive data in the form of words in written or oral form from the people and behaviors that are observed or studied. The research instrument was carried out in the form of documentation and observation (read and note) conversations in the independent student exchange group whatsapp group 1. The research data collection techniques were carried out through observation techniques and note-taking techniques. Based on the analysis of the types of code-mixing, it was found that the inner code-mixing the insertion language with elements of regional languages ??(Makassar, Minang, Bengkulu Malay), outer code-mixing the insertion with foreign language elements (Arabic and English), and hybrid code mixing insertion with foreign language elements. and regional languages ??(Makassar, Minang, Javanese, Sundanese) as well as foreign languages ??(English and Arabic) in the use of Indonesian.